Landslide Dynamics: ISDR-ICL Landslide Interactive Teaching Tools Volume 1: Fundamentals, Mapping and Monitoring (Springer International Publishing, 2018)
This interactive book presents comprehensive information on the fundamentals of landslide types and dynamics, while also providing a set of PPT, PDF, and text tools for education and capacity development. As the core activity of the Sendai Partnerships, the International Consortium of Landslides has created this two-volume work, which will be regularly updated and improved over the coming years, based on responses from users and lessons learned during its application.